Impedimetric immunosensor versus qPCR for Huanglongbing detection - Silva, Lucas Moreira [UNESP]; Martins, Elaine Cristina; Ferreira, Antonio Aparecido Pupim [UNESP]; Wulff, Nelson Arno; Yamanaka, Hideko [UNESP] (Elsevier, 2025)
Citriculture is facing challenges due to the spread of various diseases, among which the most threatening, with worldwide occurrence, is Huanglongbing (HLB), caused by the bacteria Candidatus Liberibacter spp., vectored by psyllids. In orchards, HLB-infected plants are identified by visual observation of symptoms. For laboratory diagnosis, the gold standard is the polymerase chain reaction (PCR), requiring expertise and specific equipment, and with high financial cost. In this work, a selective impedimetric immunosensor was developed for the detection and determination of Ca. L. asiaticus (CLas) in citrus samples. An anti-HLB antibody against the outer membrane protein (OMP) sequence of CLas was obtained and immobilized on previously synthesized and characterized magnetic nanoparticles. The immobilized antibody was presented to various citrus leaf sample extracts. After the affinity reaction with the antigen, a washing step was performed to minimize matrix effects. The affinity reaction was monitored by electrochemical impedance spectroscopy, using a glassy carbon working electrode containing a neodymium magnet. The developed device was able to distinguish HLB-positive samples from HLB-negative samples and those with other infections. The results obtained with the proposed methodology were in good agreement with quantitative PCR (qPCR).
Keywords: Biomolecular technique; Citriculture; Diagnoses; Electrochemical biosensor; Huanglongbing